Pristimerin Exerts Pharmacological Effects Through Multiple Signaling Pathways: A Comprehensive Review - Sun J; Tian Z; Wu J; Li J; Wang Q; Huang S; Wang M (Dove Medical Press, 2024)
Jian Sun,1,* Zhaochun Tian,2,* Jing Wu,3 Jiafei Li,3 Qixia Wang,3 Shuhong Huang,2,3 Meng Wang4 1First Clinical Medical College, Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People's Republic of China; 2Science and Technology Innovation Center, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People's Republic of China; 3School of Clinical and Basic Medical Sciences, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People's Republic of China; 4Department of General Surgery, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, Jinan, Shandong, People's Republic of China*These authors contributed equally to this workCorrespondence: Meng Wang, Department of general surgery, Affiliated Hospital of Shandong University of Traditional Chinese Medicine, 16369, Jingshi Road, Jinan, Shandong, 250014, People's Republic of China, Email wangmtcm@163.com Shuhong Huang, School of Clinical and Basic Medical Sciences, Shandong Provincial Hospital Affiliated to Shandong First Medical University, 6699, Qingdao Road, Jinan, Shandong, 250117, People's Republic of China, Email shuhonghuang@sdfmu.edu.cnAbstract: Pristimerin, a natural triterpenoid isolated from the plants of southern snake vine and Maidenwood in the family Weseraceae, is anti-inflammatory, insecticidal, antibacterial, and antiviral substance and has been used for its cardioprotective and antitumor effects and in osteoporosis treatment. These qualities explain Pristimerin's therapeutic effects on different types of tumors and other diseases. More and more studies have shown that pristimerin acts in a wide range of biological activities and has shown great potential in various fields of modern and Chinese medicine. While Pristimerin's wide range of pharmacological effects have been widely studied by others, our comprehensive review suggests that its mechanism of action may be through affecting fundamental cellular events, including blocking the cell cycle, inducing apoptosis and autophagy, and inhibiting cell migration and invasion, or through activating or inhibiting certain key molecules in several cell signaling pathways, including nuclear factor κB (NF-κB), phosphatidylinositol 3-kinase/protein kinase B/mammalian-targeted macromycin (PI3K/Akt/mTOR), mitogen-activated protein kinases (MAPKs), extracellular signal-regulated protein kinase 1/2 (ERK1/2), Jun amino-terminal kinase (JNK1/2/3), reactive oxygen species (ROS), wingless/integrin1 (Wnt)/β-catenin, and other signaling pathways. This paper reviews the research progress of Pristimerin's pharmacological mechanism of action in recent years to provide a theoretical basis for the molecular targeting therapy and further development and utilization of Pristimerin. It also provides insights into improved treatments and therapies for clinical patients and the need to explore pristimerin as a potential facet of treatment.Keywords: pristimerin, signaling pathway, pharmacological effects, review